Seismic perspectives from the western U.S. on magma reservoirs underlying large silicic calderas - Schmandt, Brandon; Jiang, Chengxin; Farrell, Jamie (Journal of volcanology and geothermal research, 2019)
Since 1.25 Ma, three volcanic systems in the western U.S. Cordillera hosted rhyolitic eruptions of ≳300 km3 dense rock equivalent creating the Yellowstone (0.63 Ma), Long Valley (0.76 Ma), and Valles (1.25 Ma) calderas. Their similar time scales since caldera-forming eruptions and rich histories of seismic research motivate a review of seismic constraints on the modern magma reservoirs beneath these calderas from the uppermost mantle to the upper crust. Across the Cordillera upper mantle seismic velocities are generally below the continental average and each of the calderas is underlain by exceptionally low velocities consistent with the presence of mantle melt, ≲3%. Concentrated upper mantle low-velocity anomalies are found beneath the eastern Snake River plain southwest of Yellowstone caldera and beneath Long Valley caldera. Valles caldera is located above a broadly distributed low-velocity anomaly associated with the Rio Grande Rift and Jemez volcanic lineament. At lower crustal depths potential magma reservoirs exhibit weaker seismic velocity anomalies and greater variability among the results of different tomographic inversion methods compared to shallower depths. At middle-to-upper crustal depths, ~5–15 km, seismic tomography provides evidence of magmatic reservoirs beneath all three calderas, and scattered wave imaging supports sharp upper, lateral, and/or lower boundaries of each inferred magma reservoir. Estimates of average melt fractions in these reservoirs vary from ~9–23% based on recent tomography, with localized melt fraction estimates as high as ~30–60% based on sharp interfaces detected by scattering and ray bending analyses. The wide range of inferred melt fractions likely results from contrasting sensitivities of different seismic imaging methods combined with spatially heterogeneous melt fractions and uncertainties in mapping seismic velocities to silicate melt fractions. Seismic radial anisotropy beneath Yellowstone and Long Valley calderas indicates that middle-to-upper crustal reservoirs are organized as sill complexes with relatively crystal-poor and crystal-rich layers, suggesting magma storage in many weakly connected volumes. Future estimates of (an)isotropic seismic velocities and melt fractions across 3D reservoirs may be improved through expanded applications of full waveform tomography to body and surface waves and increasingly dense array studies facilitated by combinations of broadband and rapidly-deployable shorter-period seismographs. Advanced seismic imaging offers potential for improved delineation of magma reservoir boundaries and constraints on intra-reservoir structures such as sill complexes that provide insight into magma reservoir mechanics and compositional heterogeneity. •Review of seismic imaging beneath the Yellowstone, Long Valley, and Valles calderas•Ongoing supply of mantle melt is likely, particularly at Yellowstone and Long Valley.•Imaging in the lower crust is more variable between methods than in the upper crust.•Evidence of a middle-to-upper crustal magma reservoir, ~5–15 km, at each system•Anisotropy at ~5–15 km depth suggests magma organized in sill complexes.